Simulative Comparison between Electric and Thermal Powertrains on Different Real Road Missions - Damiani, Lorenzo; Dellachà, Jacopo; Repetto, Matteo; Prato, Alessandro Pini (Journal of Technology Innovations in Renewable Energy, 2015)
Pure electric mobility is still struggling to emerge in the present road vehicles scenario. This is mostly due to costs, nowadays still very high, and to battery range, which is intrinsically very limited with respect to the fuel tank of a traditional vehicle. To be effectively competitive, e-mobility should not be thought as the mere substitution of the thermal powertrain with the electric one on the same vehicle; instead, a holistic approach comprehensive of the integration of a charging network within the territory should be adopted. The vehicles should be tailored on the missions to be accomplished promoting the lightness, simplicity and low cost, and should be integrated within a charging infrastructure and a car-sharing system implemented in the reference territory. In this paper the authors aim at exposing their idea of e-mobility, justifying it by simulations carried out on three different vehicles (a Diesel-fuelled Renault Kangoo, an electric driven Renault Kangoo and an electric micro-vehicle Renault Twizy) and experimental data. The simulations were carried out with the help of a validated road vehicle model in different real road missions, namely a urban, an extra-urban and a mountain mission.